Pemanfaatan Pangan Lokal Sebagai Upaya Meningkatkan Ketahanan Pangan Nasional : Dodol Tomat di Desa Margaluyu Kecamatan Pangalengan Kab. Bandung - Amelia, Lenny; Aryasuta, Dimas; Nabilah, Feranisa (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
The utilization of local food resources to enhance national food security has become a primary focus in addressing global challenges such as climate change and international market fluctuations. This outreach activity focuses on the production of tomato dodol in Margaluyu Village, Pangalengan District, Bandung Regency, as a solution to strengthen national food security. Tomato dodol was chosen due to the abundant and nutritionally valuable local tomatoes, which can be processed into healthy and nutritious food products. The goal of this activity is to introduce tomato dodol as a beneficial alternative to broaden the choices of nutritious food consumption while supporting public health. Utilizing a (Community Based Participatory Research) CBPR approach, the activity ensures active community involvement at every stage, improving production and marketing skills. The evaluation and sustainability of the program support local economic development and public health in a sustainable manner. The outcomes of this activity include increased community knowledge about the benefits of tomato dodol, reduced reliance on food imports, and contributions to strengthening national food security through the optimal use of local resources.